Autonomous Robot Microcontroller Based Obstacle Detection AT C52 - Anggar Prihandoyo (Jurnal Sistem Informasi, 2006)
Robot obstacle detection is a form of mobile robot's mission is to follow a track or path of the wall that has been determined. In the design and implementation, the problems to be solved is a robot vision system, hardware architecture (hardware) which includes electronic and mechanical devices, and software organizations (software) for the base of knowledge and control in real time. The purpose of this final task is to design and implement a Automomous Robot Microcontroller Based Obstacle Detection AT C52. Software organization of events using a base time is set to save the use of time. Source of knowledge of the encoding robot action must be done by robots based on information from sensors.